2020
DOI: 10.3390/rs12091391
|View full text |Cite
|
Sign up to set email alerts
|

Earth Observation and Cloud Computing in Support of Two Sustainable Development Goals for the River Nile Watershed Countries

Abstract: In September 2015, the members of United Nations adopted the 2030 Agenda for Sustainable Development with universal applicability of 17 Sustainable Development Goals (SDGs) and 169 targets. The SDGs are consequential for the development of the countries in the Nile watershed, which are affected by water scarcity and experiencing rapid urbanization associated with population growth. Earth Observation (EO) has become an important tool to monitor the progress and implementation of specific SDG targets through its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The SRTM was an international collaboration by NASA in 2000 to map a complete near-global high-resolution data of Earth's elevation [14]. This one-time mission mapped the topography of the Earth's surface using radar interferometry through a two-antenna setup onboard satellite.…”
Section: Srtm Demmentioning
confidence: 99%
“…The SRTM was an international collaboration by NASA in 2000 to map a complete near-global high-resolution data of Earth's elevation [14]. This one-time mission mapped the topography of the Earth's surface using radar interferometry through a two-antenna setup onboard satellite.…”
Section: Srtm Demmentioning
confidence: 99%
“…Following the methods in [38,39], harmonic analysis was applied to show a yearly trend followed by precipitation, ET and surface soil moisture in global drylands from 1 January 2000 to 31 December 2019 using monthly values (units in mm). The units of SSM/ET outputs from FLDAS and GLDAS products were also transformed into mm to compare with MODIS products.…”
Section: Harmonic Analysismentioning
confidence: 99%
“…Such expansion of big data revolutionized our understanding of the Earth system, while posing a higher request for advances in data management and processing capability. Accordingly, increasing the availability of cloud-based computing and analytical platforms, such as Amazon Web Service (AWS) and Google Earth Engine [34], is being widely used for dryland research [35][36][37][38][39][40]. Using the tools within Google Earth Engine, it was found that global dryland tree cover was significantly underrated and recent estimates exceeded previous ones by over 40% [41].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an emerging increase in high-performance cloud computing platforms, such as the NASA Earth Exchange (NEX), Amazon Web Service (AWS) and Google Earth Engine (GEE) [15]. GEE is widely used for the environmental research in the Nile watershed and adjacent regions [10,[16][17][18][19][20]. It is characterized as an easily accessible and user-friendly frontend platform providing a convenient environment for interactive data representation and algorithm development.…”
Section: Sustainable Development Goals For the River Nile Watershed Cmentioning
confidence: 99%
“…For the purpose of finding the relationship between Chl-a and NPP for each model, we developed correlation maps that show the standard correlation using the Pearson correlation coefficient (7) in the range from −1 (anti-correlation) to +1 (perfect correlation), between these two monthly time series x and y, with N elements as: (19) with Cov being the covariance function, 0̅ and ;the average and 6 @ and 6 A the standard deviations for x and y, respectively.…”
Section: Correlative Maps Between Chl-a and Npp Productsmentioning
confidence: 99%